GAMBARAN PERSEPSI BEBAN KERJA PERAWAT DI INSTALASI GAWAT DARURAT RUMAH SAKIT WILAYAH SLEMAN - Nirmalasari, Dewi (Journal of Health Service Management, 2024)
Background : Nurses in the Emergency Department (ED) have a higher workload compared to nurses in other units due to the increase in patient numbers, insufficient nursing staff, complex cases, time demands, and limited facilities. Therefore, regular workload assessments are crucial to optimize performance and healthcare service quality. Objective : This study aimed to understand the perception of nurse workload in the ED of hospitals in the Sleman region. Method : This research was a descriptive analytical study with a cross-sectional approach involving 122 nurses in the ED of Sleman Regional Hospital. The study measured nurses' workload perception using Nursalam's (2017) nurse workload questionnaire, covering job activities, types of tasks, and time usage. Univariate analysis was used to describe respondents' characteristics and nurses' workload perception in four EDs in the Sleman region, including RSUP Dr. Sardjito, RSA UGM, RSUD Sleman, and RS PKU Muhammadiyah Gamping. Result : The research findings indicated that the average perception of nurse workload in the ED of Sleman Regional Hospital was 30,8 (SD±9,2), interpreted as a moderate workload. Job activities emerged as the highest domain with an average of 11,3 (SD±3,7) and the statement item with the highest average was direct nurse-patient contact in the ED at 2,7 (SD±1). Conclusion : The overall perception of nurse workload in the ED of Sleman Regional Hospital indicated a moderate workload. The results of this research could serve as a basis for the hospital's ED in formulating policies related to nurse workload.